Phonophobia and hyperacusis: practical points from a case report - Asha'ari, Zamzil Amin; Mat Zain, Nora; Razali, Ailin (Universiti Sains Malaysia, 2010)
Phonophobia and hyperacusis are two separate but closely related symptoms that are often mistakenly used in clinical practice as the same entity. Here we present a case report to highlight the distinguishing features of both and discuss the steps of management in these conditions. It is vital for the attending doctors to recognise hyperacusis and phonophobia as different entities to manage them successfully.